2002
DOI: 10.1128/mcb.22.24.8601-8611.2002
|View full text |Cite
|
Sign up to set email alerts
|

A C-Terminal Inhibitory Domain Controls the Activity of p63 by an Intramolecular Mechanism

Abstract: The human genome is far smaller than originally estimated, and one explanation is that alternative splicing creates greater proteomic complexity than a simple count of open reading frames would suggest. The p53 homologue p63, for example, is a tetrameric transcription factor implicated in epithelial development and expressed as at least six isoforms with widely differing transactivation potential. In particular, p63␣ isoforms contain a 27-kDa C-terminal region that drastically reduces their activity and is of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
220
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(234 citation statements)
references
References 49 publications
14
220
0
Order By: Relevance
“…Surprisingly, the DNp51B transgenic mouse did not exhibit clear abnormality of the skin. This implies that TAp51B is much more potent inhibitor of Notch1 than DNp51B considering the fact that TAp51B is a much more labile protein than DNp51B (Serber et al, 2002). We do not have a plausible explanation for this discrepancy other than that the transgenic experiment was designed to express the proteins in early embryonic stages, whereas we used keratinocytes of much later stages.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Surprisingly, the DNp51B transgenic mouse did not exhibit clear abnormality of the skin. This implies that TAp51B is much more potent inhibitor of Notch1 than DNp51B considering the fact that TAp51B is a much more labile protein than DNp51B (Serber et al, 2002). We do not have a plausible explanation for this discrepancy other than that the transgenic experiment was designed to express the proteins in early embryonic stages, whereas we used keratinocytes of much later stages.…”
Section: Discussionmentioning
confidence: 97%
“…Otherwise, it is attractive to speculate the involvement of an inhibitory domain residing in the COOH-terminus of p51B isoforms (Serber et al, 2002). Interestingly, DNp51B binds to inhibitor kappa B kinase (IKK)a through the COOH-terminus region triggering keratinocyte differentiation (Enjo et al, submitted) and many of the p51 mutation found among human hereditary syndromes reside in the COOH-terminal domain ( (Celli et al, 1999;McGrath et al, 2001;Duijf et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the isoforms contain a Sterile Alpha-Motif (SAM) and a Trans Inhibitory Domain (TID). The former is a protein-protein interaction domain, also present in other molecules [10,11], while the latter is an inhibitory domain that blocks transactivation by masking a few residues on the N-terminal TA, (it could also be responsible for oligomerisation between different p63 isoforms) [12].…”
Section: Trp63 Gene Organization and P63 Protein Structurementioning
confidence: 99%
“…24 In the a-splice forms of p63 and p73, a long stretch of amino acids (119 in p63 and 109 in p73) connects the OD to a sterile alpha motif (SAM) domain, which is followed by a transcriptional inhibitory domain. 12,25 Several invertebrate p53 proteins also contain long C-terminal stretches, however, with low sequence identity to the mammalian family members. Surprisingly, in the p53 forms of the two important model organisms, Caenorhabditis elegans (CEP-1) and Drosophila melanogaster (Dmp53), this low sequence identity includes the otherwise highly conserved OD.…”
mentioning
confidence: 99%